2014
DOI: 10.6018/eglobal.13.3.196531
|View full text |Cite
|
Sign up to set email alerts
|

Factores que influyen en la realización de una episiotomía selectiva en mujeres nulíparas.

Abstract: Nº 35 Julio 2014Página 398 ENFERMERÍA Y PERSPECTIVA DE GÉNERO Factores que influyen en la realización de una episiotomía selectiva en mujeres nulíparasFactors affecting the performance of a selective episiotomy in nulliparous women *Hernández Pérez, Javier **Azón López, Esther ***Mir Ramos, Eduardo ****Peinado Berzosa, Ruth *****Val Lechuz, Belén ******Mérida Donoso, RESUMENObjetivo: Determinar los factores que influyen en la realización de una episiotomía selectiva en mujeres nulíparas. Material y método:Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The main strength of our study was that caregivers/health professionals were provided with training on the different types of tears to be able to classify them correctly. This aspect was overlooked in other studies (18,39). A limitation of this study was that other variables reported in other studies such as maternal age, maternal weight, maternal height (40), maternal pathology, perineal protection (15), newborn biparietal diameter (14) duration of first stage of labour, duration of second stage of labour (40) and clinicians’ attitudes were not studied (14,40).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The main strength of our study was that caregivers/health professionals were provided with training on the different types of tears to be able to classify them correctly. This aspect was overlooked in other studies (18,39). A limitation of this study was that other variables reported in other studies such as maternal age, maternal weight, maternal height (40), maternal pathology, perineal protection (15), newborn biparietal diameter (14) duration of first stage of labour, duration of second stage of labour (40) and clinicians’ attitudes were not studied (14,40).…”
Section: Discussionmentioning
confidence: 82%
“…There is conflicting evidence regarding the relationship on the use of epidural analgesia and the performance of an episiotomy. While some studies demonstrate an association (15,19), other studies do not demonstrate a statistically significant relationship (18). The association of epidural analgesia and severe perineal damage have also been reported (15,24) but this is also controversial, with another study not showing any relationship between these factors (25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study carried out with 568 nulliparas in a tertiary hospital in Zaragoza, Spain, in the group that did not have an episiotomy, there was a significant increase of first-degree tears compared to second-degree tears (55.6% and 15.7%, respectively), without causing any risk to fetal well-being (22) . The results were similar in the present study, in terms of slight perineal tears which, if necessary, may be sutured by an obstetric nurse, with a perineal outcome without clinical complications.…”
Section: Discussionmentioning
confidence: 97%
“…The male gender was found to be another independent risk factor of an episiotomy in our study. However, in a Spanish study by Hernandez et al (2014) [ 34 ] and the study from Ethiopia by Marai (2002) [ 35 ], no difference between the sex of the child and the episiotomy procedure was shown.…”
Section: Discussionmentioning
confidence: 99%